2012
DOI: 10.1007/s00221-012-3104-x
|View full text |Cite
|
Sign up to set email alerts
|

Perception of maximum reaching height reflects impending changes in reaching ability and improvements transfer to unpracticed reaching tasks

Abstract: Perception of whether a given behavior is possible typically reflects a person's action capabilities even before the behavior is performed and even when the person has undergone recent changes to their action capabilities. Importantly, perception of affordances for a given behavior also reflects impending changes to action capabilities. Two experiments investigated perception of affordances for reaching when the means of reaching would bring about changes in reaching ability. Experiment 1 found that perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
37
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 31 publications
4
37
0
1
Order By: Relevance
“…The fact that both canine and human perception of affordances for reaching reflects a task specific fit between action capabilities and environmental properties despite such differences between the reaching behaviors used by these species may 2 Rearing by canines may, perhaps, be more analogous to a human reaching from one foot or while standing on tip toes. Importantly, human perception of affordances for reaching under such circumstances also scales to action capabilities (see Fisher, 2000;Wagman, 2012). only serve to strengthen the support for the claim that perception of this affordance is supported by detection of a task-specific stimulation patterns that is invariant across species.…”
Section: Limitations and Future Directionsmentioning
confidence: 66%
See 2 more Smart Citations
“…The fact that both canine and human perception of affordances for reaching reflects a task specific fit between action capabilities and environmental properties despite such differences between the reaching behaviors used by these species may 2 Rearing by canines may, perhaps, be more analogous to a human reaching from one foot or while standing on tip toes. Importantly, human perception of affordances for reaching under such circumstances also scales to action capabilities (see Fisher, 2000;Wagman, 2012). only serve to strengthen the support for the claim that perception of this affordance is supported by detection of a task-specific stimulation patterns that is invariant across species.…”
Section: Limitations and Future Directionsmentioning
confidence: 66%
“…In addition, research on perception of affordances by humans has also shown that maximum reaching distance tends to be overestimated (Carello et al, 1989;Fischer, 2000;Heft, 1993), but tends to increasingly reflect action capabilities with repeated perceptual experience (Ramenzoni, Davis, Riley, & Shockley, 2008;Wagman, 2012). Given that our methodology required presenting the treat at a height that was scaled to each dog and resulted in one data point per participant (the rearing boundary), it is not possible to investigate either phenomena with the current data.…”
Section: Limitations and Future Directionsmentioning
confidence: 90%
See 1 more Smart Citation
“…Persepsi merupakan pengalaman tentang obyek, peristiwa atau hubungan-hubungan yang diperoleh dengan menyimpulkan informasi dan menafsirkan pesan (Rakhmat, 2013). Persepsi seseorang berbeda tergantung pada apa yang dialami oleh pelaku, baik yang sudah terjadi maupun sedang terjadi (Wagman, 2012). Dengan menggunakan skala likert, maka variabel yang akan diukur dijabarkan menjadi dimensi, dimensi dijabarkan menjadi indikator yang dapat diukur (Riduwan, 2008).…”
Section: Analisis Dataunclassified
“…For instance, Stoffregen, Yang, Giveans, Flanagan, and Bardy (2009) found that practice locomoting with a wheelchair resulted in more accurate judgments of the minimum lintel that could be passed under, even though pass-under-ability was not explicitly practiced. Similarly, Wagman (2012) found that practice in overhead reach ing while standing on toes improved the perception of reaching with an object without standing on toes. Also, perceptual training on perceived length of rods by dynamic touch transfers to per ceived location of the center of percussion of the rods (Withagen & Michaels, 2007); despite that, Cooper, Carello, and Turvey (1999) found that reports of length and center of percussion were perceptually independent.…”
mentioning
confidence: 91%